Stigmatizing Attitudes Toward Depression Among Male and Female, Medical and Non-medical Major College Students - He, Haoyu; Wu, Qiuxia; Hao, Yuzhu; Chen, Shubao; Liu, Tieqiao; Liao, Yanhui (Frontiers in Psychology, 2021)
Background Stigma is often reported to be a barrier for the treatment and rehabilitation of depression. However, little is known about stigma towards people with depression among college students in China. Methods Using a questionnaire with a case vignette describing depression, a total of 1056 students from 9 colleges/universities in Hunan Province of China were included in this study. The questionnaire addressed the attitudes towards depression and the desire for distance from depressed individuals. The current study explored college students’ stigma attitudes towards people with depression and the desire for social distance, as well as the gender (male and female) and major (medical and non-medical) differences. Results Over half of the respondents agreed that people described in the vignette were “dangerous” (60.7%) and "could snap out of the problem” (58.7%). Compared with female students, males were more likely to agree that “If I had this problem, I wouldn't tell anyone” (7.0% vs. 13.2%, p = 0.001); compared with non-medical students, medical students were more likely to agree that “The problem is a sign of personal weakness” (38.0.% vs. 50.0%, p  0.001). A lot of respondents would be unwilling to “marry into the family of people with depression” (71.1%) or “work closely to them” (45.1%). Compared with male students, females were more unwilling to “work closely to them” (40.3% vs. 47.5%, p = 0.026). Conclusion This study found that a high proportion of Chinese college students showed stigma towards and desire for social distance from people with depression, male students and medical major students showed higher stigma in some subscale items towards people with depression. The present results suggest that more anti-stigma interventions should be applied for Chinese college students to help prevent or reduce stigma attitudes towards people with depression.